Deleuze and design - Marenko, Betti; Brassett, Jamie (Deleuze connections., 2015)
"Whether we are dealing with products or scenarios, packaging or experiences, territories or digital platforms, design is never a thing but a process of change, invention and speculation that always has material, tangible implications that affect behaviours and lives. Drawing on a range of contributors, case studies and examples, this book examines ways in which we can think about design through Deleuze, and how Deleuze's thought can be experimented upon and re-designed to produce new concepts. This book taps into the emerging networks between philosophy as an act of inventing concepts and design as the process of inventing the world."--